Pelatihan Asesmen Diagnostik Non-Kognitif untuk Guru MGMP IPA sebagai Pendukung Implementasi Kurikulum Merdeka Belajar Pengenalan Karakter Siswa - Iramadhani, Dwi; Safriana; Astuti, Widi; Muna, Zurratul; Dwi Puspa, Cindy; Syahridha, Putri Ulfah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
improvement, and qualitative and quantitative evaluations were carried out. Result: In general, the participants gave a very good rating to the first speaker. The participants also gave a qualitative assessment of this training. Teachers find out the crucial conditions of students that can ultimately help students in the learning process. Pre-tests and post-tests were also carried out in this service in the form of tests of teachers' knowledge of PBIS learning methods. The mean pre-test score was 21.06 and the mean post-test score was 23.66. Conclusion: Furthermore, the conclusion is this training is able to effectively increase teachers' knowledge related to Non-Cognitive Diagnostic Assessment for Lhokseumawe City Science MGMP teachers as a support to the implementation of Merdeka Learning Curriculum for Student Character Recognition.